Pendampingan Pembuatan E-LKPD Menggunakan Platform Liveworksheet bagi Guru Matematika SMP - Hasibuan, Riswandi; Tanjung, Hasyim Ansari; Hoiriyah, Diyah (Ngarsa: Journal of Dedication Based on Local Wisdom, 2024)
The service team was encouraged to assist in making Electronic Student Worksheets using the Liveworksheet platform for mathematics teachers at SMPN 9 Padangsidimpuan. Even though this remote school supports learning technology, teachers still need help creating and implementing technology-based learning effectively, thus hampering optimal teaching and learning processes. The aim is to provide insight into the knowledge of making Electronic Student Worksheets using the live worksheet platform in classroom building material for class VIII. This service activity is divided into three stages: preparation, implementation, and evaluation, with each stage demonstrating the steps for using the live worksheet application in mathematics learning. Teacher mentoring activities in preparing Electronic Student Worksheets using the live worksheet platform show that the teachers of SMPN 9 Padangsidimpuan have gained valuable new knowledge and skills. This activity succeeded in broadening the insight and skills of mathematics teachers in using Electronic Student Worksheets as a practical and creative learning tool. Keywords: Student Worksheets, Liveworksheets, Mathematics Teachers, Junior High School Abstrak: Tim pelaksana pengabdian terdorong mengadakan pendampingan pembuatan Lembar Kerja Peserta Didik Elektronik (E-LKPD) menggunakan platform Liveworksheet bagi guru matematika di SMPN 9 Padangsidimpuan. Meskipun sekolah terpencil ini mendukung teknologi pembelajaran, para guru masih kesulitan membuat dan menerapkan pembelajaran berbasis teknologi secara efektif, sehingga menghambat proses belajar mengajar yang optimal. Tujuannya adalah memberikan wawasan pengetahuan tentang pembuatan E-LKPD menggunakan platform liveworksheet pada materi bangun ruang kelas VIII. Kegiatan pengabdian ini dibagi menjadi tiga tahapan, yaitu tahapan persiapan, tahapan pelaksanaan, dan tahapan evaluasi dengan setiap tahapannya mendemonstrasikan langkah-langkah penggunaan aplikasi liveworksheet dalam pembelajaran matematika. Kegiatan pendampingan guru dalam penyusunan E-LKPD menggunakan platform liveworksheet menunjukkan bahwa guru-guru SMPN 9 Padangsidimpuan telah memperoleh pengetahuan dan keterampilan baru yang bermanfaat. Kegiatan ini berhasil memperluas wawasan dan keterampilan guru matematika dalam menggunakan E-LPKD sebagai alat pembelajaran yang praktif dan kreatif. Kata kunci: Lembar Kerja Peserta Didik, Liveworksheet, Guru Matematika, Sekolah Menengah Pertama